The exception in the agency on behalf relatives between the civil and criminal cases - Turki Awwad, Assistant Professor Dr. Qasim (The college of law and political science journal, 2023)
The general principle is for the same person to initiate ligation procedures ,or to appoint one of lawyers registered in the lawyers roll, as it is not permissiblefor others to give legal advice or delegate on behalf of others to claim and defendrights before public and special courts, investigation departments, police andcommittees designated by law to investigate or dismiss in judicial disputes, butit is permissible for the attorney not to a lawyer, but rather a relative to undertakeWKHMXGLFLDOSURFHGXUHVLQÀOLQJWKHFDVHEHIRUHWKHFRPSHWHQWFRXUWVXEPLWWLQJrequests in it and following it up in all stages of litigation, whether it is in the civillawsuit or in the criminal lawsuit, or is the matter different between the two lawsuits,as there is an exception for the representation of relatives in one of them withoutWKHRWKHUDQGZKHWKHUWKLVH[FHSWLRQZDVPHQWLRQHGLQVSHFLÀFODZVXLWVRULVLWDQXQVSHFLÀHGH[FHSWLRQZKLFKZLOOEHH[SODLQHGLQWKLVEULHIUHVHDUFK